2011
DOI: 10.1080/02705060.2011.555212
|View full text |Cite
|
Sign up to set email alerts
|

Competitive interactions between walleye (Sander vitreus) and smallmouth bass (Micropterus dolomieu) under various controlled conditions

Abstract: The range of smallmouth bass (Micropterus dolomieu) is expanding northward, creating new interactions with native predators, including walleye (Sander vitreus). We used a series of experiments to investigate competition between walleye (WAE) and smallmouth bass (SMB) at different life stages and light conditions, identified behaviors that allowed one fish to outcompete another, and evaluated whether prey switching mitigated competitive interactions. Juvenile and adult SMB appeared to outcompete WAE when fed du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 39 publications
3
15
0
Order By: Relevance
“…A more recent study by Galster et al (2012) analysed stable carbon and nitrogen isotope changes in walleye before and after smallmouth bass colonization in four lakes and found that walleye tissue became more nitrogen-rich and carbon-negative after colonization, indicating a shift in consumption of benthic to pelagic prey. It is possible that this shift occurs because smallmouth bass display competitive territorial behaviour in the presence of other predators, which could exclude walleye from near-shore prey resources (Wuellner et al, 2011;Galster et al, 2012). This agonistic behaviour could have negative effects on walleye populations in smaller lakes where prey is limited, as smallmouth bass have been found to be more effective predators under preylimiting conditions (Wuellner et al, 2011).…”
Section: Implications Of Climate Change On Biotic Interactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…A more recent study by Galster et al (2012) analysed stable carbon and nitrogen isotope changes in walleye before and after smallmouth bass colonization in four lakes and found that walleye tissue became more nitrogen-rich and carbon-negative after colonization, indicating a shift in consumption of benthic to pelagic prey. It is possible that this shift occurs because smallmouth bass display competitive territorial behaviour in the presence of other predators, which could exclude walleye from near-shore prey resources (Wuellner et al, 2011;Galster et al, 2012). This agonistic behaviour could have negative effects on walleye populations in smaller lakes where prey is limited, as smallmouth bass have been found to be more effective predators under preylimiting conditions (Wuellner et al, 2011).…”
Section: Implications Of Climate Change On Biotic Interactionsmentioning
confidence: 99%
“…It is possible that this shift occurs because smallmouth bass display competitive territorial behaviour in the presence of other predators, which could exclude walleye from near-shore prey resources (Wuellner et al, 2011;Galster et al, 2012). This agonistic behaviour could have negative effects on walleye populations in smaller lakes where prey is limited, as smallmouth bass have been found to be more effective predators under preylimiting conditions (Wuellner et al, 2011).…”
Section: Implications Of Climate Change On Biotic Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides angling pressure, stockpiling can become problematic for a variety of other reasons (Wilde 1998). Black bass are voracious predators that may be able to outcompete other predatory fish near the release site (Wuellner et al 2011). They may also locally deplete prey fish, resulting in lower black bass growth rates and smaller size at age near the release site, especially when one release site is repeatedly used for multiple tournaments over the course of a season (Ricks and Maceina 2008).…”
mentioning
confidence: 99%
“…Due to their short residence time, relatively little is known about Smallmouth Bass interactions with native species in most South Dakota waters. However, several studies have examined potential predatory and competitive interactions between Smallmouth Bass and Walleye in field and laboratory settings as a response to angler concerns that bass were preying on juvenile Walleyes and reducing abundance, condition, and growth rates of adult Walleyes via interspecific resource competition (Wuellner et al 2010(Wuellner et al , 2011a(Wuellner et al , 2011bGalster et al 2012). While few studies have assessed the impact of Smallmouth Bass predation on prey fish populations, several have documented bass food habits in state waters (e.g., Lott 1996;Blackwell et al 1999;Bacula 2009), which may provide insight into potential predatory impacts.…”
mentioning
confidence: 99%